Application of Jigsaw technique in improving students’ integrated skills: An action research project on the 10th-grade students at a high school in Hung Yen = Sử dụng kĩ thuật mảnh ghép (Jigsaw) trong việc phát triển kĩ năng tích hợp của học si - Bùi, Thị Thu Nhung (2019)
Mastering all four language skills is very essential to successful communication, and is the main target of all language learners. Understanding this need and the problems that learners face during learning English, this action research was conducted with the aim at improving students‟ integrated skills through Jigsaw technique to the tenth grade students of Nguyen Sieu High School in the academic year of 2017-2018 and investigating their attitudes toward this technique.